<=> 4(x^2 + 2x + 1) + 4x^2 - 4x +1 - 8(x^2 - 1) = 11
<=> 4x^2 + 8x + 4 + 4x^2 - 4x +1 - 8x^2 +8 - 11 = 0
<=> 4x + 2 = 0
<=> x = - 1/2
\(4\left(x+1\right)^2+\left(2x-1\right)^2-8\left(x-1\right)\left(x+1\right)=11\)
\(4\left(x^2+2x+1\right)+4x^2-4x+1-8\left(x^2-1\right)=11\)
\(4x^2+8x+4+4x^2-4x+1-8x^2+8=11\)
\(4x+13=11\)
\(4x=-2\)
\(x=-\frac{1}{2}\)
4(x+1)2 + (2x-1)2- 8(x-1)(x+1) = 11
<=>4x2 + 8x + 4 + 4x2 - 4x + 1 + 8x2 + 8 - 11 = 0
<=>4x+ 2 =0
<=>x = 1/2
Vậy phương trình đã cho có tập nghiệm S = { 1/2}